2011
DOI: 10.1159/000322312
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Base of Articulation for Consonants among Catalan Dialects

Abstract: Electropalatographic data for several front lingual consonants, i.e., the dental /t/, the alveolars /n, l, s, r/ and the alveolopalatals /t.,∫ ∫, λ, η/, show differences in constriction anteriority among Catalan dialects varying in the progression Valencian > Eastern, with the Majorcan dialect occupying an intermediate position. These differences do not conform to speaker- dependent differences in palate morphology and, to the extent that they operate on a varied range of consonants, may be attributed to base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For example, Bradlow (1995) demonstrated across-the-board fronting (higher second formant frequencies) of English /i, e, o, u/ relative to their Spanish counterparts. Similarly, Recasens (2010) demonstrated dialect-specific constriction anteriority for several front lingual consonants, /t, n, l, s, r, ʧ, ʃ, ʎ, ɲ/, among Catalan dialects. In each of these cases, the documented language- or dialect-dependent differences in articulatory setting prevailed over talker-specific differences.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, Bradlow (1995) demonstrated across-the-board fronting (higher second formant frequencies) of English /i, e, o, u/ relative to their Spanish counterparts. Similarly, Recasens (2010) demonstrated dialect-specific constriction anteriority for several front lingual consonants, /t, n, l, s, r, ʧ, ʃ, ʎ, ɲ/, among Catalan dialects. In each of these cases, the documented language- or dialect-dependent differences in articulatory setting prevailed over talker-specific differences.…”
Section: Introductionmentioning
confidence: 85%
“…Specifically, the fronted articulatory setting for English relative to Spanish vowels could not be attributed to cross-talker variation in vocal tract length, which would have resulted in parallel shifts for all formant frequencies rather than just for the second formant (Bradlow, 1995). Similarly, for the consonant study (Recasens, 2010) the dialect-specific articulatory setting could not be attributed to individual variation in palate morphology. Instead, studies such as these have demonstrated a group-level, learned, articulatory setting, or language/dialect-specific phonetics.…”
Section: Introductionmentioning
confidence: 90%
“…It is hard to know the extent to which these differences in formant frequency reflect differences in darkness or else are associated with speaker-dependent differences in vocal tract size and/or palate height. Data on palate curvature for the five speakers under analysis reveal no obvious relationship between formant frequency and the height of the palatal vault which suggests that the former option is more plausible than the latter (Recasens, 2010). Thus, for example, while exhibiting the flattest palate of all speakers, speaker DP does not differ radically from the other subjects regarding the F1 and F2 frequency values for [ɫ] (see the top and bottom right graphs of Figure 3).…”
Section: Consonant Midpointmentioning
confidence: 84%
“…It is likely that there are some language-dependent indexical cues to speaker identity which were lost with the language switch. Languages or even dialects can have different bases-of-articulation for 'phonemically equivalent' sounds (Bradlow 1995;Disner 1983;Jacewicz 1999Jacewicz , 2002Recasens 2010;Torreira and Ernestus 2011). It should be noted that these differences are not linguistically contrastive or meaningful in these languages; they are just different 'settings' .…”
Section: Discussionmentioning
confidence: 99%